Plan de mejoramiento de los procesos de manipulación y almacenamiento en las bodegas de Mercancía de Olímpica S.A. Distrito Cafetero (2017)
The storage and handling of goods processes in the warehouses of trading companies are critical to their operation. If these processes are carried out in inappropriate ways, they can result in unsatisfaction from the final consumers, as well as economic losses to the organization. Reason why in Olimpica S.A. how these processes were carried out was studied in order to find and correct deficiencies, resulting in greater customer satisfaction and better profit margins for the organization.